1975
DOI: 10.1152/ajplegacy.1975.228.6.1868
|View full text |Cite
|
Sign up to set email alerts
|

Glycerokinase in mammalian adipose tissue: stimulation by lipogenic substances

Abstract: A connecting link between carbohydrate and fat metabolism in adipose tissue is theconcentration of alpha-glycerophosphate derived predominantly from the glycolysis ofglucose entering the fat cell. However, several investigators have reported the presence of a glycerol specific kinase in the epidiymal fat-pad of the rat and obob mouse.This enzyme's presence in other mammalian adipose tissue could contribute to the alpha-glycerophosphate pool and thus affect both carbohydrate and fat metabolism within the fat ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1976
1976
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Indeed, PEPCK-C expression is stimulated by ␤-agonists and in the fasting state (21), whereas GyK expression is not (7,22), arguing for GNG as the major physiological pathway involved in the control of FA output from human SCAT. This greater implication of GNG is in agreement with what Chen et al (23) recently observed in vivo in young mice fed a low carbohydrate diet in which GNG was by far the predominant pathway leading to G3P synthesis for TG accumulation in fat.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PEPCK-C expression is stimulated by ␤-agonists and in the fasting state (21), whereas GyK expression is not (7,22), arguing for GNG as the major physiological pathway involved in the control of FA output from human SCAT. This greater implication of GNG is in agreement with what Chen et al (23) recently observed in vivo in young mice fed a low carbohydrate diet in which GNG was by far the predominant pathway leading to G3P synthesis for TG accumulation in fat.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to adipocyte-specific genes such as aP2, glycerol kinase (GyK) is normally expressed at low levels in white adipose tissue (Wieland and Suyter 1957;Treble and Mayer 1963;Persico et al 1975;Sargent et al 1994), but is markedly up-regulated by TZD treatment of adipocytes (Guan et al 2002;Tordjman et al 2003;Patsouris et al 2004). GyK catalyzes the phosphorylation of glycerol to produce glycerol-3-phosphate, the backbone for esterification of FFAs in the production of triglycerides (TGs).…”
mentioning
confidence: 99%
“…Brown adipose tissue from the newborn rabbit [10] like white adipose tissue [20] from adult animals has low glycerol kinase activi ty. When glycerol kinase is absent the glyc erol released by hydrolysis of triglyceride is not metabolized in the cell, and passes into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%